Efficacy and safety of anti-interleukin 6 receptor monoclonal antibody (tocilizumab) in Colombian patients with Takayasu arteritis. (2014)
Purpose: The aim of this study was to describe the efficacy and safety of anti–interleukin 6 receptor antibody (tocilizumab [TCZ]) in patients with severe or refractory Takayasu arteritis (TA). Methods: We describe 8 Colombian patients with severe and/or refractory TA treated with TCZ during a period of at least 9 months. Clinical, radiological, biological, and associated treatments were evaluated before, during, and after TCZ infusions. Results: The median age at evaluation was 31 years (12–43 years). All patients were female and experienced clinical and biological improvement, in addition to a corticosteroid-sparing effect from a median dose of 50 mg/d at baseline (30–60 mg/d) to 6.25 mg/d (2.5–10 mg/d) at 9 months. In 4 cases, in which imaging studies were available, an improvement was observed.